Mucosal-Associated Invariant T Cell Interactions with Commensal and Pathogenic Bacteria: Potential Role in Antimicrobial Immunity in the Child - Ghazarian, Liana; Caillat-Zucman, Sophie; Houdouin, Véronique (Frontiers in Immunology, 2017)
Mucosal-associated invariant T (MAIT) cells are unconventional CD3+ CD161high T lymphocytes that recognize vitamin B2 (riboflavin) biosynthesis precursor derivatives presented by the MHC-I related protein, MR1. In humans, their TCR is composed of a Vα7.2-J33/20/12 chain, combined with a restricted set of Vβ chains. MAIT cells are very abundant in the liver (up to 40% of resident T cells) and in mucosal tissues, such as the lung and gut. In adult peripheral blood, they represent up to 10% of circulating T cells, whereas they are very few in cord blood. This large number of MAIT cells in the adult likely results from their gradual expansion with age following repeated encounters with riboflavin-producing microbes. Upon recognition of MR1 ligands, MAIT cells have the capacity to rapidly eliminate bacterially infected cells through the production of inflammatory cytokines (IFNγ, TNFα, IL-17) and cytotoxic effector molecules (perforin, granzyme B). Thus, MAIT cells may play a crucial role in antimicrobial defense, in particular at mucosal sites. In addition, MAITs have been implicated in diseases of non-microbial etiology, including autoimmunity and other inflammatory diseases. Although their participation in various clinical settings has received increased attention in adults, data in children are scarce. Due to their innate-like characteristics, MAIT cells might be particularly important to control microbial infections in the young age, when long-term protective adaptive immunity is not fully developed. Herein, we review the data showing how MAIT cells may control microbial infections and how they discriminate pathogens from commensals, with a focus on models relevant for childhood infections.